Development of Criminal Evidence Law in Indonesia - Gea, Ali Yusran (LEGAL BRIEF, 2024)
Proof is a form of description relating to the truth of an event so that an acceptable truth status is obtained, apart from that, proof is also the act of proving. The evidentiary system is a regulation of the types of evidence that may be used. Proving whether the defendant actually committed the act charged is the most important part of the criminal procedure. There are 4 (four) theories of evidence known in the history of evidentiary law, namely Positive Wettelijk Bewijstheorie, Conviction In Time, Conviction Raisonne and Negative Wettelijk Bewijstheorie. The evidence system in Indonesia adheres to a negative system of evidence according to law (negatief wettelijk bewijstheorie) where evidence must be based on law, namely with at least two valid pieces of evidence. The judge obtains confidence that a criminal act actually occurred and that the defendant was guilty of doing it. The development of evidence in proving criminal acts in Indonesia, both those that have been regulated in special legislation and those that are purely based on the Criminal Procedure Code, has certainly had an impact on progress for law enforcement in Indonesia